CFD Analysis of UAV Flying Wing - Vasile PRISACARIU (INCAS Bulletin, 2016)
Numerical methods for solving equations describing the evolution of 3D fluid experienced a significant development closely related to the progress of information systems. Today, especially in the field of fluid mechanics, numerical simulations allow the study of gas-thermodynamic confirmed by experimental techniques in wind tunnel conditions and actual flight tests for modeling complex aircraft. The article shows a case of numerical analysis of the lifting surface on the UAV type flying wing.